Fishermen's Insurance Program In Bandar Lampung City Based On An Institution Perspective - Octavia, Nia; Supono, Supono; Damai, Abdullah Aman; Abidin, Zainal; Febryano, Indra Gumay (Universitas Bangka Belitung, 2025)
The low sustainability of participation in the Fishermen’s Insurance Premium Assistance program shows that there is an Institution issue. The research intents to analyze the institution of the fishermen’s insurance program in Bandar Lampung City. This study used the case study method as a qualitative approach. Data were obtained by in-depth interviews, participant observation, and document analysis. Analysis is used to describe institutions based on situation, structure, behavior, and performance. The results of the study show that the efforts of the insurance program in Bandar Lampung City to protect fishermen have not been achieved in the second year. This occurred because the insurance participants did not pay the premium independently or at personal expense. The fishermen are not interested in participating in insurance, in spite of the premium cost being economical. Institutions are included in the BPAN program, which plays an important role in determining the continuation of fishermen’s insurance participation. The government should consider the punishment and agreements that must be submissive by fishermen to become effective regulation. In addition, the Social Security Administrator for Employment, as an insurance provider, must accommodate the simple insurance premium payments for fishermen.